The Association Between Deaf Identity and Emotional Distress Among Adolescents. (8th February 2020) - Lambez, Tal; Nagar, Maayan; Shoshani, Anat; Nakash, Ora
Abstract: The sociocultural approach regards being deaf as a cultural characteristic in the identity of a deaf/hard-of-hearing (D/HH) person. The degree to which one integrates the hearing and Deaf cultures ("acculturation") is an important factor for the well-being of deaf adolescents. We examined the relationship between acculturation patterns and emotional distress among D/HH ( n = 69) compared to hearing ( n = 60) adolescents in Israel. We used culturally and linguistically accessible measures. Our findings showed no significant differences in emotional distress between D/HH and their hearing counterparts. Acculturation played an important role predicting emotional distress. Identification with both the Deaf and hearing cultures was associated with reduced somatization. Exposure to discrimination and social support was also associated with emotional distress in predictable ways. Findings are interpreted within the specific context of Israeli society and highlight the importance of using adaptive linguistic and cultural assessment tools with D/HH populations.